PENGARUH PENGGUNAAN ALAT PERAGA SMART STICK TERHADAP HASIL BELAJAR MATEMATIKA MATERI BANGUN RUANG PADA SISWA KELAS V SEKOLAH DASAR - Septiani, Tarisa Dwi; Taufik, Mirna; Jaya, Melinda Puspita Sari (STKIP Persada Khatulistiwa Sintang, 2024)
Smart Stick teaching aids are teaching aids made of wooden sticks used to make spatial geometry frames. This study aims to determine the effect of using smart stick teaching aids on spatial geometry material on Mathematics learning outcomes of grade V at elementary school. This research method uses True Experimental with Post-test Only Control Design. The sampling of this study used a random sampling technique consisting of two classes, namely class VB and VC, totaling 45 students. Based on the results of the average value obtained by class VB of 84.35 and class VC of 70. Hypothesis testing of this research data uses an independent sample t-test, obtained with a value of tcount> ttable, obtained 3.62> 1.68 and sig. (2 tailed) = 0.001 <0.05. It can be interpreted that there is an effect of using smart stick teaching aids on spatial geometry material on Mathematics learning outcomes at grade V in SD Negeri 21 Palembang.